The 3D type book - Jacquillat, Agathe; Vollauschek, Tomi (Laurence King Publishing, 2011)
A handbook, source of inspiration and comprehensive showcase which focuses solely on three-dimensional experimental letterforms, this book describes sculptural, shape-shifting letters, tactile experiences and surprising and inventive ways to interpret the alphabet